Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA)—from morphology to molecular testing - Righi, Luisella; Franzi, Francesca; Montarolo, Francesca; Gatti, Gaia; Bongiovanni, Massimo; Sessa, Fausto; La Rosa, Stefano (Journal of Thoracic Disease, 2017)
In recent years, endobronchial ultrasound-guided TBNA (EBUS-TBNA) has emerged as an innovative technique for diagnosis and staging of lung cancer and has been successfully introduced into daily clinical practice with several advantages including minimally invasive approach, safe, cost-effective, real time image guidance, broad sampling capability, and rapid on-site evaluation (ROSE). Both cytological and histological approach could be useful to have material for diagnosis, immunohistochemical and molecular analyses which may be very important for targeted therapy with successful rate ranging from 89% to 98%. The utility of ROSE during EBUS-TBNA has been matter of debate. Indeed, although some evidence concluded that ROSE does not increase the diagnostic efficacy of EBUS-TBNA, other demonstrated that it improves the diagnostic yield of the procedure up to 30%, allows to avoid repetition of additional diagnostic procedures and reduces risk of complications. Furthermore the sample preparation by cytopathologist is optimized with the aid of direct macroscopic inspection, optimal smearing techniques, and triage of the sample permitting to obtain adequate tissue for diagnosis, ancillary techniques and molecular testing, when needed. Some pathological issues on EBUS-TBNA are reviewed and discussed with particular focus on ROSE and molecular testing